[Coconut Picker] - (:unkn) unknown (M. Jolly, Trinidad, 2009)
This is a picture of a man climbing a coconut tree with a rope hanging from his waist which he uses to lower the coconuts from the tops of the trees. A description on the back of the postcard reads "Green drinking coconuts must be cut from the palms - often a high climb; the rope is used to lower the nuts gently." Postcard numbered C7588.
Colour: Coloured; Style: Portrait; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Coconut palm--Trinidad and Tobago; Agriculture--Trinidad and Tobago; Working class--Trinidad and Tobago; Tree climbing--Trinidad and Tobago